Assesment of urban sustainable development: example of Rezekne city (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Since 90s of the 20th century sustainable development has become a global issue which is receiving increasing attention. Successful sustainable development is only possible from the bottom to the top, which means that the human and environmental mutual relations must be taken into account not only on a global scale as a whole, but also focus on the much smaller territorial units.The role of the city as the administrative territorial unit has significantly increased in recent years, the acknowledgment for that can be found in the European Union Cohesion Policy, polycentric development policy, spatial planning policy, etc., in the figures of the rapid population growth in urban areas, about joining of separate scientific disciplines in order to study current issues in the cities.In sustainable development studies special attention is paid to mega cities or capitals, which have the most significant impact on the environment, based on certain key indicators - CO2 emissions, the amount of municipal solid waste generated in cities, etc.The planning documents, that provide a picture of the specific urban sustainable development priorities, play an important role in ensuring sustainable development.The aim of the article is to explore the sustainable development strategies of the city of Rezekne for 2013-2030 in conformity with the five dimensions of sustainable development and to assess the development possibilities of Rezekne.During the study the sustainable development strategy of Rezekne for 2013-2030 was evaluated, strategic aims, long-term priorities, and actions were established. As a result, it was concluded that they meet all five dimensions of sustainable development, but in the strategy for these actions, it is necessary to focus on the essence of the concept of sustainable development, that meets the needs of the present without compromising the ability of future generations to meet their own needs [1].The evaluation of current performance shows that the strategy of planned targets may not materialize and as a result have a significant impact on sustainable development, so it is necessary to make appropriate adjustments in the operational plans.